ANALISIS RISIKO KANDUNGAN ZINC (Zn) DALAM KEPITING BAKAU DI SUNGAI TAPAK KOTA SEMARANG - Norma Arinda Kesuma; Sulistiyani Sulistyani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Tapak River is one of the rivers in Semarang city that used for the provision of fresh water and agricultural irrigation channels. Tapak river contain many heavy metals, one of them is Zn which come from domestic waste and industrial wase. The purpose of this research is to analyze the risk of Zn content in who consuming mangrove crab in Tapak River, Semarang City. The type of this research is observational with Environmental Health Risk Analysis (EHRA) approach. The population of the subject is 98 residents who consumed the crab and a population of objects is the levels of Zn in the mangrove crab. The sample of the subjects are 50 residents who consume mangrove crab and the sample of the object is the levels of Zn in mangrove crabs from Tapak River. The Data analysis use EHRA stages. The results of this research show the concentration Zn in the mangrove crabs is 21,43 mg/kg. The average weight of respondents is 59.96 kg, with an average frequency of exposure per year is 107,12 days per year, the average duration of exposure was 18,88 years, the average realtime intake is 0,0154 mg/kg/days and lifetime intake is 0,0224 mg/kg/days and the average of realtime risk quotient is 0,515 and lifetime is 0,0746 on ingested pathways. The conclusion is the concentration of Zn in the mud crabs at Tapak River is above the quality standard of Minister of Environment Decree Number 51 of 2004 which is 0.05 mg/kg, but it does not cause chronic effects nor acute, and the average realtime and lifetime exposure on respondents is <1 and declared safe to consume until 30 years to go.